Writing systems for Italian regional languages*. Issue 6 (3rd July 2019) - Coluzzi, Paolo; Brasca, Lissander; Miola, Emanuele
ABSTRACT: Devising a writing system, or graphisation, is a fundamental aspect of corpus planning that no language can take too lightly. This paper begins with a general introduction to graphisation and to Italian regional languages, followed by an analysis of the different orthographies in use so far or proposed for the main regional languages in Italy, with reference also to the three Romance languages already accorded official recognition as minority languages: Sardinian, Friulian and Ladin. The practical aspect and the symbolic aspect of graphisation are discussed and the problems and difficulties that are being encountered in this process are highlighted, especially with regard to two Northern varieties that are presented as case studies: Lombard and Piedmontese. The paper closes with some general considerations and recommendations, particularly on the adoption of a polynomic approach to graphisation if at all possible, and of a digraphic regime as a transitional strategy for cases where a common orthography cannot be decided upon, or to help the spread of the language among new speakers.